Pengenalan Alat Scann Machine untuk Latihan Passing pada Sepak Bola - Sutrisna Sutrisna; Andri Irawan; Raisa Ganeswara (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out how to create a scanning machine tool and a training model using a scanning machine tool for passing accuracy in football. The research method used in this research is the ADDIE model research and development (R & D) method. The stages carried out in the research were 5 stages, namely 1.) Analysis, 2.) Design, 3.) Development, 4.) Implementation, 5.) Evaluation. The research subjects for the implementation of the scanning machine tool and the training model with the tool were 20 players from the Football and Futsal Club (KSBF) of Jakarta State University. In this research, researchers collaborated with 3 experts, namely technical director, coach of the Estrelass Del Futbol (EDF) Academy and electronics expert. The validation test used in this research was a justification test consisting of 3 experts. After the expert validation test is carried out, the next step is the implementation of the scan machine tool and the training model with the scan machine tool. The result of this research is the creation of a product and guidebook of a scanning machine.